It should never happen here a guide for minimizing the risk of child abuse in ministry - Zarra, Ernest J. 1955- (Grand Rapdis, MI Baker, 1997)
Includes bibliographical references.
Keywords: Child sexual abuse -- prevention; Church personnel management